STUDENTS’ ORGANISATIONAL EXPERIENCE AND THEIR SPEAKING-CONFIDENCE OF ENGLISH - Yusuf, Kamal; Hilmun, Perisya (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Joining student organizational activities is positively impacts both extrinsically and intrinsically, such as developing leadership or good speaking skills. Several studies have been conducted to examine the role of student organizations in increasing their confidence when speaking. However, many of these studies rely only on general self-confidence but not in the context of classroom learning. The purpose of this study was to analyze students' speaking confidence in class and the correlation between students' organizational experience and their speaking confidence. This type of research is quantitative research. The population in this study found 35 students. The instrument used in this research is a questionnaire. The technique used to analyze the data is the Pearson Product Moment Correlation to determine the relationship between the independent variable (organizational experience) and the determinant variable (self-confidence). The results of this study indicate that the significance level (0.001) and Pearson correlation = 0.569 (sig = 0.01). This shows a significant relationship between the organization and a high level of self-confidence in class. It can be said that the organizational experience of students can increase their sense of self-confidence.